Isolation and comparison of Escherichia coli strains from canine and human patients with urinary tract infections. - Low, D A (1988)
We analyzed Escherichia coli strains isolated from dogs with urinary tract infections (UTIs) in an attempt to determine if any of these strains were similar to E. coli isolated from humans with UTIs. Using genotypic and phenotypic traits, we identified four canine and six human E. coli UTI isolates that all appeared to be closely related or identical. All isolates shared similar DNA sequences for pyelonephritis-associated pili (pap), alpha-hemolysin (hly), and insertion sequence 5 (IS5), on the basis of Southern blot analysis. Similar outer membrane protein, pilin, and plasmid profiles were obtained for each of the isolates, although minor heterogeneity was observed. All of these isolates expressed a neuraminidase-sensitive binding phenotype in contrast to the majority of human isolates, which are known to express an adhesin that recognizes terminal digalactoside residues. Taken together, these results suggest that similar E. coli uropathogens may be capable of infecting both dogs and humans. To determine if the intestinal tracts of dogs were a reservoir for uropathogenic E. coli, eight paired rectal and urine pap+ E. coli strains were cultured from dogs with UTIs. By using the same genotypic and phenotypic criteria described above as a basis for strain identity, seven of eight urine-rectal pairs showed intrapair identity. However, each urine-rectal pair displayed a unique overall profile and could be distinguished from the other pairs. We conclude that the uropathogen colonizing the bladders of dog can also be the predominant strain colonizing the intestinal tracts.